The development of functional glutamatergic and GABAergic synaptic connections between vestibulo-ocular projection neurons and oculomotor motoneurons in the chicken embryo - Hiraku Mochida; Joel C. Glover (Frontiers in Neurology)
Introduction and methodsWe assessed the functional development of synapses from defined vestibulo-ocular projection neurons to motoneurons (MNs) in the oculomotor nuclear complex in the chicken embryo using optical recording of postsynaptic responses with the calcium-sensitive probe Calcium Green Dextran Amine (CGDA). The vestibulo-ocular projection neuron groups were defined according to the hodological nomenclature established by Díaz et al. (1) and encompassed the ipsilateral rostral, ipsilateral caudal and contralateral caudal vestibulo-ocular (iR-VO, iC-VO and cC-VO) groups. These groups provide differential input to the inferior rectus (IR), superior oblique (SO), superior rectus (SR) and inferior oblique IO) MN pools. The cC-VO group includes abducens interneurons (abd INs) which innervate the medial rectus (MR) MN pool. Since the SO MN pool, which projects out the trochlear nerve, was not labeled, recordings were limited to the IR, SR, IO and MR MN pools.ResultsSingle pulse stimulation of all the presynaptic axons collectively in wholemount preparations of the brain stem elicited robust calcium responses in all four of the CGDA-labeled postsynaptic MN pools. Responses were recorded from the dorsal surface in different regions of interest (ROIs) deployed along the mediolateral axis, which allowed us to distinguish responses in IR, MR+IO and SR MNs. Responses were first detected in a fraction of preparations at d7 of development, and from d8 in all preparations. Response magnitudes increased through d9, and then diminished through d11. Pharmacological experiments showed that responses included both glutamatergic (AMPA receptor and NMDA receptor-mediated) and GABAergic (GABAA receptor-mediated) components. All three components were present when the first responses appeared, but their proportional contribution changed during development. Covert NMDA-sensitive responses could be revealed by superfusing unresponsive d7 preparations with Mg2+-free Ringer, indicating that the very first responses to develop were mediated by NMDA receptors. GABAergic responses involved the activation of voltage-gated calcium channels and were therefore likely to be depolarizing, but nevertheless had an inhibitory effect on glutamatergic responses. Paired pulse and train stimulation at d9-d11 demonstrated substantial facilitation of the aggregate response.DiscussionThese data provide new information about the functional development of vestibulo-ocular reflex (VOR) circuitry and set the stage for testing the role of specific receptors and downstream signaling in establishing the specific synaptic connections that characterize the VOR.